Wartości utrwalone w nazwach ulic (na przykładzie Częstochowy i Humania) = Values recorded in street names (on the example of Częstochowa and Uman) - Pyvovar, Liliia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Comparative analysis has been subject to the naming of streets of Częstochowa and Uman. Selected localities have different naming systems. The analysis was aimed at showing the values preserved in Polish and Ukrainian street names (on the example of two selected cities). The empirical part of the research material consists of 1206 street names of Częstochowa and 284 plateonyms of Uman.
Keywords: nazewnictwo ulic; wartości; analiza porownawcza; Częstochowa; Humań; street names; values; comparative analysis; Uman